COMET: a new end‐station at SOLEIL for coherent magnetic scattering in transmission. (18th December 2018) - Popescu, H.; Perron, J.; Pilette, B.; Vacheresse, R.; Pinty, V.; Gaudemer, R.; Sacchi, M.; Delaunay, R.; Fortuna, F.; Medjoubi, K.; Desjardins, K.; Luning, J.; et al.
Abstract : The new COMET experimental station dedicated to soft X‐ray coherent scattering imaging techniques at the SEXTANTS beamline of the SOLEIL synchrotron is presented. The instrument and its performance are illustrated with examples of holography and ptychography imaging of magnetic domains. Abstract : A new instrument named COMET for COherent Magnetic scattering Experiments in Transmission using polarized soft X‐rays has been designed and built. This high‐vacuum setup is placed at the intermediate focal point of the elastic branch of the SEXTANTS beamline at Synchrotron SOLEIL. The main application is in solid state physics, the instrument being optimized for studying material properties using coherent scattering of soft X‐rays with an emphasis on imaging, with chemical selectivity, the magnetic domains of artificially nano‐structured materials. The instrument's principal features are presented and illustrated through recently performed experiments.